Menciptakan Niat Membeli Kembali Melalui Kepuasan Pelanggan: Studi Peran Pengalaman Merek, Brand Authenticity, dan Brand Equity - Maulina Kurniawati; Puji Astuti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Creating customer satisfaction is a primary goal of business activities, as the continuity of the business depends on its customers. This study aims to eksplore the relationships between brand experience, brand authenticity, brand equity, customer satisfaction, and repurchase intention within the smartphone industry in the Jabodetabek region. A quantitative approach is employed using an online survey and a Likert scale-based questionnaire. The study population includes users of Samsung, Oppo, and Xiami Android smartphones, with a purposive sample of 210 respondents aged 18-45. Data were analyzed using the Covariance-Based Structural Equation Modeling (CB-SEM) and factor analysis to test validity and reliability.. The results reveal that brand experience significantly influences brand authenticity and brand equity, with brand authenticity also affecting brand equity. Brand equity positively impacts customer satisfaction. However, brand authenticity and brand experience do not significantly affect customer satisfaction. Customer satisfaction has a positive effect on repurchase intention. The model demonstrates a good fit according to the established criteria. The conclusion of this study is that brand experience, brand authenticity, and brand equity significantly impact customer satisfaction and repurchase intention. This research provides valuable insight for developing marketing strategies in the smartphone industry, emphasizing the importance of creating a positive and consistent brand experience and building strong brand authenticity. The study also notes some limitations, suggests further research with a broader geographic range and mixed methods for more comprehensive results.